2020
DOI: 10.1017/s2045796020000050
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and health services' usage in children with autism spectrum disorder: a nested case–control study

Abstract: Aims Children with autism spectrum disorder (ASD) tend to suffer from various medical comorbidities. We studied the comorbidity burden and health services' utilisation of children with ASD to highlight potential aetiologies and to better understand the medical needs of these children. Methods In this nested case–control study, ASD cases and controls – matched by age, sex and ethnicity in a 1:5 ratio – were sampled from all children born between 2009 and 2016 at a tertiary medical centre.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…Further contributing to this heterogeneity is the observation that individuals with ASD also commonly have a range of comorbid conditions. These include other NDDs (e.g., attention deficit hyperactivity disorder [ADHD] [Dizitzer et al, 2020; Lai et al, 2019], obsessive compulsive disorder [OCD] [Lai et al, 2019; van Steensel, Bogels, & de Bruin, 2013]), and multiple psychiatric conditions (e.g., anxiety, depression [Kirsch et al, 2020; Lai et al, 2019; van Steensel et al, 2013], schizophrenia [Houghton, Ong, & Bolognani, 2017; Kirsch et al, 2020; Lai et al, 2019], and bipolar disorder [Kirsch et al, 2020; Lai et al, 2019]). Individuals with ASD are also more likely to be diagnosed with a host of other medical conditions including epilepsy [Lukmanji et al, 2019], gastrointestinal disturbances [Brondino et al, 2019; Dizitzer et al, 2020; Lee et al, 2018], sleep disorders [Croen et al, 2015], diabetes [Croen et al, 2015; Flygare Wallén, Ljunggren, Carlsson, Pettersson, & Wändell, 2018], hypertension [Croen et al, 2015; Flygare Wallén et al, 2018], and respiratory diseases [Cawthorpe, 2017] among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further contributing to this heterogeneity is the observation that individuals with ASD also commonly have a range of comorbid conditions. These include other NDDs (e.g., attention deficit hyperactivity disorder [ADHD] [Dizitzer et al, 2020; Lai et al, 2019], obsessive compulsive disorder [OCD] [Lai et al, 2019; van Steensel, Bogels, & de Bruin, 2013]), and multiple psychiatric conditions (e.g., anxiety, depression [Kirsch et al, 2020; Lai et al, 2019; van Steensel et al, 2013], schizophrenia [Houghton, Ong, & Bolognani, 2017; Kirsch et al, 2020; Lai et al, 2019], and bipolar disorder [Kirsch et al, 2020; Lai et al, 2019]). Individuals with ASD are also more likely to be diagnosed with a host of other medical conditions including epilepsy [Lukmanji et al, 2019], gastrointestinal disturbances [Brondino et al, 2019; Dizitzer et al, 2020; Lee et al, 2018], sleep disorders [Croen et al, 2015], diabetes [Croen et al, 2015; Flygare Wallén, Ljunggren, Carlsson, Pettersson, & Wändell, 2018], hypertension [Croen et al, 2015; Flygare Wallén et al, 2018], and respiratory diseases [Cawthorpe, 2017] among others.…”
Section: Introductionmentioning
confidence: 99%
“…The increased burden of comorbid conditions makes meeting the needs of these patients more complex, and corresponds to increased health system utilization compared to the general population [Dizitzer et al, 2020]. In fact, patterns of comorbidities have been shown to identify subgroups of ASD with distinct clinical trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most cited problems has been the confounding role of the intellectual disability (ID). This group also has increased the number of CMPD in ASD [3,8]. A selection bias to study people with ASD without ID was shown [68,69].…”
Section: Why Is the Progress So Slow In Practice When So Much Is Known From Published Research?mentioning
confidence: 99%
“…Recent manuscripts reviewed the so-called comorbidities in ASD [4,5]. Comorbidities may be psychiatric [6], neurological [7], or related to medical conditions beyond the brain in the field of Pediatrics or General Medicine [8]. Recent literature has demonstrated that people with ASD diagnosis may have multiple comorbidities in different combinations and severity [9] and even temporal, transient hyper-multimorbidity.…”
Section: Introduction-the Backgroundmentioning
confidence: 99%
“…The prevalence of ASD is estimated to be 1.7-1.85% of children and adolescents [1][2][3]. Children with ASD have a variety of comorbidities that affect their functioning during their daily lives [4]. Especially, sleep disturbances are relatively common and affect not only the daily functioning and quality of life of children but also the quality of life of their family [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%